Thrombotic microangiopathy in patients with sickle cell disease - Gabriella Biasi Carrasco; Patricia Belintani Blum; Josefina Aparecida Pellegrini Braga (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To describe two cases of patients who had thrombotic microangiopathy (TMA) associated with sickle cell disease (SCD). Case description: Both patients started with a painful crisis and had acute chest syndrome during hospitalization. They showed significant worsening of hemolytic anemia, with very high levels of lactate dehydrogenase, thrombocytopenia, lowered level of consciousness, organ damage and the presence of schistocytes in peripheral blood. Due to the possibility of TMA, despite the very rare association with SCD, they were treated with fresh frozen plasma replacement and plasmapheresis, with good response. Comments: TMA is a serious, life-threatening disease, characterized by microangiopathic hemolytic anemia, thrombocytopenia, and organ damage. The association of SCD and TMA is difficult to diagnose, since they can share a similar clinical presentation. Recognizing this association and promptly instituting treatment may impact the survival of these patients.